Within‐species reproductive costs affect the asymmetry of satyrization in Drosophila. (22nd November 2015) - Yassin, A.; David, J. R.
Abstract: Understanding how species interactions influence their distribution and evolution is a fundamental question in evolutionary biology. Theory suggests that asymmetric reproductive interference, in which one species induces higher reproductive costs on another species, may be more important in delimiting species boundaries than interspecific competition over resources. However, the underlying mechanisms of such asymmetry remain unclear. Here, we test whether differences in within ‐species reproductive costs determine the between ‐species asymmetry of costs using three allopatric Drosophila species belonging to the melanogaster subgroup. Our results support this hypothesis, especially in a pair of insular species. Males of one species that induce costs to their conspecific females led to a 5‐fold increase of heterospecific females mortality with dead flies bearing spectacular large melanized wounds on their genitalia. Males of the other species were harmful neither to their conspecific nor heterospecific females. Comparative studies of within ‐species reproductive costs may therefore be a valuable tool for predicting between ‐species interactions and community structures.